The influence of German loanwords on the Upper Silesian dialect with a special emhasize on culinary vocabulary - Tomecka, Magdalena (Free your mind: Reflections on language, literature and culture, 2022)
Upper Silesia is an extremely important region in our homeland. For centuries, it has been a temptation for many countries, including Poland and Germany. This was mainly due to its favourable geographical location and the natural wealth of the region. The constant battles between the two countries and the intermingling of many cultures in this territory have shaped the original language of the people of Upper Silesia, which is based primarily on two languages: Polish and German. Because Silesia, by virtue of the Yalta Treaty, has belonged since the end of the Second World War to the territory of the Republic of Poland, it is treated as an important part of the state being.  It should be emphasized that the whole Silesian dialect, including all its dialects, is based on the Polish language system, and any elements from the German language are treated as borrowings. The main aim of the research was to focus on the issue of German borrowings from the culinary field which appear in the Upper Silesian dialect and which are listed in the "Dictionary of Silesian dialects" by Barbara and Adam Podgórski. It was also important to show to what extent words from the German language occur in this dialect and how their borrowing process proceeds.